2017
DOI: 10.1016/j.radonc.2016.06.015
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of Caphosol mouthwash in management of radiation-induced mucositis in head and neck cancer

Abstract: Caphosol did not reduce the incidence or duration of severe OM during and after radiotherapy in HNC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 18 publications
(20 reference statements)
3
43
0
1
Order By: Relevance
“…In all studies, the oncologic treatment method is described: chemotherapy [2], combined chemotherapy and radiotherapy [3,10,11], radiotherapy [11], chemotherapy [12,13,14], combined chemotherapy and radiotherapy [15,16], radiotherapy [17,18], combined chemotherapy and radiotherapy [18], chemotherapy [19], combined chemotherapy and radiotherapy [20], radiotherapy [20], chemotherapy [21], combined chemotherapy and radiotherapy [22,23], radiotherapy [24], combined chemotherapy and radiotherapy [25], radiotherapy [26], combined chemotherapy and radiotherapy [27], chemotherapy [28]. …”
Section: Methodsmentioning
confidence: 99%
“…In all studies, the oncologic treatment method is described: chemotherapy [2], combined chemotherapy and radiotherapy [3,10,11], radiotherapy [11], chemotherapy [12,13,14], combined chemotherapy and radiotherapy [15,16], radiotherapy [17,18], combined chemotherapy and radiotherapy [18], chemotherapy [19], combined chemotherapy and radiotherapy [20], radiotherapy [20], chemotherapy [21], combined chemotherapy and radiotherapy [22,23], radiotherapy [24], combined chemotherapy and radiotherapy [25], radiotherapy [26], combined chemotherapy and radiotherapy [27], chemotherapy [28]. …”
Section: Methodsmentioning
confidence: 99%
“…A search for recently published articles about SCPR identified a large RCT, which concluded that SCPR was ineffective in the management of OM in H&N cancer patients treated with RT/RT-CT [83]. A recent RCT in pediatric patients [84] and comparative studies about SCPR indicated conflicting results about the effectiveness in preventing OM [23,85].…”
Section: Discussionmentioning
confidence: 99%
“…Benzydamine (a locally acting topical nonsteroidal anti‐inflammatory) was also demonstrated to decrease OM when compared to saline mouth wash daily during RT with the greatest effect in reducing oral pain . Caphasol, which is marketed to lubricate the mouth for xerostomia, did not result in any decrease in mucositis when provided during RT . Finally, in a single dose study, the use of doxepin (a tricyclic antidepressant) or “Magic Mouth Wash” (lidocaine‐containing rinse) each compared to placebo noted decreased oral pain in the first 60 minutes with either experimental agent, whereas those receiving doxepin had increased fatigue compared to placebo …”
Section: Discussionmentioning
confidence: 99%
“…42 Caphasol, which is marketed to lubricate the mouth for xerostomia, did not result in any decrease in mucositis when provided during RT. 43 Finally, in a single dose study, the use of doxepin (a tricyclic antidepressant) or "Magic Mouth Wash" (lidocaine-containing rinse) each compared to placebo noted decreased oral pain in the first 60 minutes with either experimental agent, whereas those receiving doxepin had increased fatigue compared to placebo. 44 Taken together, the results reported here are suggestive of a protective effect of D-met in preventing OM.…”
Section: Discussionmentioning
confidence: 99%